2015
DOI: 10.1038/eye.2014.312
|View full text |Cite
|
Sign up to set email alerts
|

The development and evolution of full thickness macular hole in highly myopic eyes

Abstract: Purpose To evaluate the morphological changes before and after the formation of a full-thickness macular hole (MH) in highly myopic eyes. Patients and methods Retrospective observational case series. From 2006 to 2013, clinical records of patients with MH and high myopia who had optical coherence tomography (OCT) before the development of MH were reviewed. All patients had been followed for more than 1 year since MH formation to observe the morphological changes.Results Twenty-six eyes of 24 patients were enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 30 publications
2
27
0
1
Order By: Relevance
“…The risk of developing FTMH (25%) was much higher than patients with idiopathic LMH (1%-4%) [5,17]. Similar as our previous report [4], the progression of LMH to FTMH may have achieved through different mechanisms in this group; it may come from (1) tangential premacular traction due to epiretinal membrane (Fig 1L), (2) abnormal vitreofoveal anteroposterior traction ( Fig 1N), and (3) macular atrophy with underlying scar.…”
Section: Plos Onesupporting
confidence: 81%
See 2 more Smart Citations
“…The risk of developing FTMH (25%) was much higher than patients with idiopathic LMH (1%-4%) [5,17]. Similar as our previous report [4], the progression of LMH to FTMH may have achieved through different mechanisms in this group; it may come from (1) tangential premacular traction due to epiretinal membrane (Fig 1L), (2) abnormal vitreofoveal anteroposterior traction ( Fig 1N), and (3) macular atrophy with underlying scar.…”
Section: Plos Onesupporting
confidence: 81%
“…Importantly, the present study revealed that LMH with retinoschisis had a more unstable clinical course compared to MTM (progression rate: 48.5% vs. 17%-28%) [13,21]. As described in the literature [4,6], the evolution of LMH to FD or FTMH in the present study can be further classified into two patterns: (1) formation of focal elevation of the outer retinal layer, leading to FD, with subsequent FTMH formation after rupture of the outer retina; (2) widening and/or deepening of the LMH, leading to FTMH directly. Patients who developed FD were prone to progression into FTMH, so most of them (12 out of 16 eyes, 75%) underwent surgery at this stage.…”
Section: Plos Onesupporting
confidence: 75%
See 1 more Smart Citation
“…Recently, several mechanisms regarding the development of MH in highly myopic patients were analyzed, and different pathways of MH formation were reported [ 44 ]. In detail, a normal foveal depression with abnormal vitreoretinal relationship characterized the first pathway.…”
Section: Pathogenesismentioning
confidence: 99%
“…The univariate regression analyses identified that only the female gender (P = 0.0111) was significantly associated with postoperative FAZ change. In addition to sex, we also included the axial length (univariate analysis, P = 0.1043) to the multivariate analysis, because previous studies suggested that the axial length was a risk factor of MH formation 22,23 and was also associated with the retinal structures. 24 The multivariate analysis also identified that only the female gender (P = 0.0380) was significantly associated with postoperative FAZ change.…”
Section: Relationship Between Postoperative Faz Change and Parametersmentioning
confidence: 99%